2020
DOI: 10.21037/tcr-19-2825
|View full text |Cite
|
Sign up to set email alerts
|

Super-enhancers modulate interleukin-6 expression and function in cancers

Abstract: Background: It is widely accepted that inflammatory cytokine, interleukin 6 (IL-6), was not only elevated in cancer but also important in carcinogenesis. But how did IL-6 be produced in tumor microenvironment remains to be addressed. Methods:Both bioinformatics tools and quantitative real time polymerase chain reaction (RT-PCR) were used to examine the expression of IL-6 in cancer cells. To map super-enhancers of IL-6, sgRNAs were constructed. Stable knockout cells were established and subsequently used for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, loss of TP53 protein is likely to release its transcriptional repressor activity on the IL6 promoter. Meanwhile, the TP53 R172H protein has recently been shown to induce expression of the CSF1 cytokine via an interaction with BRD4 on a histone 3 lysine 27 acetylation-rich (H3K27ac) region 49 , which is also found in a super-enhancer in the IL6 locus that is susceptible to BRD4-inhibition 50 . Indeed, epigenetic activation of this superenhancer, as judged by ATAC sequencing signals, correlated with IL6 expression in esophageal and pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, loss of TP53 protein is likely to release its transcriptional repressor activity on the IL6 promoter. Meanwhile, the TP53 R172H protein has recently been shown to induce expression of the CSF1 cytokine via an interaction with BRD4 on a histone 3 lysine 27 acetylation-rich (H3K27ac) region 49 , which is also found in a super-enhancer in the IL6 locus that is susceptible to BRD4-inhibition 50 . Indeed, epigenetic activation of this superenhancer, as judged by ATAC sequencing signals, correlated with IL6 expression in esophageal and pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) is overexpressed in pancreatic cancer. Bao et al demonstrated that genetic deletion of IL6-SEa or treatment with two inhibitors of the SE-related BET protein, JQ-1 and I-BET762, significantly reduced the IL-6 expression levels in multiple cancer cells [54].…”
Section: Se Participate In the Transcription Reprogramming Of Oncogenesmentioning
confidence: 99%